2011
DOI: 10.1002/ccd.22980
|View full text |Cite
|
Sign up to set email alerts
|

One‐year results of the INSPIRE trial with the novel MGuard stent: Serial analysis with QCA and IVUS

Abstract: In this series of patients treated with MGuard stent, the novel device showed no midterm efficacy and safety concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Actually, the membrane also prevented the endothelial ingrowth within the stent, which was eventually related to high rates of stent thrombosis as well as high rates of restenosis at the edges of the stent . In the case of the MGuard, however, it appears that the mesh does not prevent the neointimal proliferation within the stent . The rate of stent restenosis was low in our cohort.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Actually, the membrane also prevented the endothelial ingrowth within the stent, which was eventually related to high rates of stent thrombosis as well as high rates of restenosis at the edges of the stent . In the case of the MGuard, however, it appears that the mesh does not prevent the neointimal proliferation within the stent . The rate of stent restenosis was low in our cohort.…”
Section: Discussionmentioning
confidence: 68%
“…17,18 In the case of the MGuard, however, it appears that the mesh does not prevent the neointimal proliferation within the stent. 19 The rate of stent restenosis was low in our cohort. Importantly, routine angiographic follow-up was not performed and therefore we cannot rule out the occurrence of restenosis that does not provoke ischemia or symptoms in an infarcted myocardial territory.…”
Section: Discussionmentioning
confidence: 96%
“…Extracellular adenosine derives mainly from hydrolysis of ATP (primarily, but not exclusively, by the ectoenzymes CD39 and CD73) and mediates its effects via activation of G-protein-coupled receptors (A1R, A2AR, A2BR and A3R). Adenosine has long been known to regulate inflammation and immune responses78 and work from our lab and others have demonstrated the importance of adenosine and its receptors in osteoblast, osteoclast, and bone marrow homeostasis9101112131415161718192021. Prior studies have suggested that adenosine receptors also regulate chondrocyte physiology and pathology in response to inflammatory stimuli in rodent, equine, bovine and human chondrocytes2223242526 although the specific receptor(s) involved are not identified.…”
mentioning
confidence: 99%
“…Therefore, it appears that Mguard stent does not prevent neointimal proliferation. 37 Thus, further improvement in MNM technology covering stents should include a drug eluting technology for the prevention of restenosis as used by other coronary endo-protheses. The MNM interacts with the vessel wall and could therefore be used as a platform for drug coating in association with abluminal bioabsorbable polymer coating.…”
Section: Discussionmentioning
confidence: 99%